Virus replication and competition in a cell culture: Application to the SARS-CoV-2 variants. (November 2022) - Ait Mahiout, L.; Mozokhina, A.; Tokarev, A.; Volpert, V.
Abstract: Viral replication in a cell culture is described by a delay reaction–diffusion system. It is shown that infection spreads in cell culture as a reaction–diffusion wave, for which the speed of propagation and viral load can be determined both analytically and numerically. Competition of two virus variants in the same cell culture is studied, and it is shown that the variant with larger individual wave speed out-competes another one, and eliminates it. This approach is applied to the Delta and Omicron variants of the SARS-CoV-2 infection in the cultures of human epithelial and lung cells, allowing characterization of infectivity and virulence of each variant, and their comparison.